Let patients control the purse strings. Issue 7648 (10th April 2008) - Alakeson, Vidhya
Abstract : Patient choice is much talked about in the NHS and other health systems but action has been limited. Vidhya Alakeson argues that piloting individual healthcare budgets would signal real commitment to creating patient centred care